(untitled) (EAAE Annual Conference Proceedings, 2025)
In an era of ecological precarity and disciplinary fragmentation, architectural education must renew its commitment to synthesis – not merely stylistic, but as an integration of environmental, social, and spatial knowledge. This paper presents a comparative pedagogical study of two educational contexts employing Post-Occupancy Evaluation (POE) as a design and learning tool: a monodisciplinary course with architecture students, and an interdisciplinary workshop including students from architecture, mechanical engineering, psychology, business, and industrial design, both evaluating the Foreign Languages Department building at TOBB University of Economics and Technology, Ankara, Türkiye. POE remains underexplored in architectural curricula despite its value in assessing building performance and user satisfaction, and interdisciplinary learning settings are notably scarce. In the monodisciplinary course, architecture students conducted the POE themselves, applying quantitative, RIBA-based methods to evaluate thermal comfort, indoor air quality, and spatial optimization. Their retrofit proposals emphasized technical solutions like façade insulation and BIM-based energy simulations, framing the building primarily as an object to optimize. In contrast, the interdisciplinary group was provided with the earlier POE findings as a point of departure. Their emphasis was on qualitative user experiences and practical comfort. The resulting solutions prioritized ergonomic furniture, acoustic comfort, spatial flexibility, and everyday usability, informed by collaborative ideation and experience sharing rather than computational simulations. This comparative analysis reveals distinct educational outcomes: the architecture students’ value metrics and physical optimizations, while interdisciplinary teams prioritize spatial agency and practical usability. Nevertheless, both groups reframed the building as a resource for thoughtful transformation, suggesting a combined technical and user-centered approach could enrich architectural curricula. By situating students in critical dialogue with existing structures, POE-based pedagogy fosters an ethic rooted in user care, highlighting reuse supported by evidence. Integrating quantitative technical assessments with qualitative user-focused insights thus emerges as a promising strategy for enhancing architectural education.